High strength right angle composite joints for civil infrastructure. (1st January 2002) - Ellis, Gary; Van Erp, Gerard
This paper presents results from an ongoing research project that is concerned with the development of strong, semi-rigid right angle composite joints for civil engineering applications. The main purpose fo the sequential tests is to further enable comparative analysis of the geometry of the joint, in particular the inside corner, and its corresponding load carrying capacity. Experimental and numerical results for four different types of monocoque right angle joints loaded in pure bending are presented.